THE EFFECT OF DIVIDEND POLICY, PROFITABILITY, LIQUIDITY AND FIRM SIZE ON FIRM VALUE IN MANUFACTURING COMPANIES OF FOOD AND BEVERAGE SUBSECTORS - Hasugian, Christnova (International Journal of Public Budgeting, Accounting and Finance, 2019)
The objective of this study is to determine and analyse the effect of dividend policy, profitability, liquidity and firm size partially and simultaneously on firm value in food and beverage companies listed on the Indonesia Stock Exchange. The population of this research is 10 food and beverage companies listed on the Indonesia Stock Exchange with observation years 2007 to 2017. The sample was selected using the purposive sampling method. Data is processed using panel data regression statistical test methods. The results of this study prove that partially dividend policy, liquidity and firm size have a positive but not significant effect on firm value on food and beverage companies listed on the Indonesia Stock Exchange. Simultaneously, profitability has a positive and significant effect on firm value in food and beverage companies listed on the Indonesia Stock Exchange.